Drosophila: a Tale of regeneration with MYC - Serras, Florenci; Bellosta, Paola (Frontiers in Cell and Developmental Biology, 2024)
Regeneration is vital for many organisms, enabling them to repair injuries and adapt to environmental changes. The mechanisms underlying regeneration are complex and involve coordinated events at the cellular and molecular levels. Moreover, while some species exhibit remarkable regenerative capabilities, others, like mammals, have limited regenerative potential. Central to this process is the regulation of gene expression, and among the numerous genes involved, MYC emerges as a regulator of relevant processes during regeneration with roles conserved in several species, including Drosophila. This mini-review aims to provide valuable insights into the regeneration process in flies, focusing on significant organs where the role of MYC has been identified: from the imaginal discs, where MYC regulates cell growth, structure, and proliferation, to the gut, where it maintains the balance between renewal and differentiation of stem cells, and the central nervous system, where it influences the activities of neural stem cells and the interaction between glia and neuronal cells. By emphasizing the molecular mechanisms regulated by MYC, its significance in controlling regeneration mechanisms, and its conserved role in flies, we aim to offer valuable insights into the utility of Drosophila as a model for studying regeneration. Moreover, unraveling MYC's function in Drosophila during regeneration may help translate findings into the mechanisms underlying human tissue repair.